Morphological and molecular data reveal the cryptic diversity among populations of Aegla paulensis (Decapoda, Anomura, Aeglidae), with descriptions of four new species and comments on dispersal routes and conservation status - Moraes, Juliana Cristina Bertacini; Terossi, Mariana; Buranelli, Raquel Corrêa; Tavares, Marcos; Mantelatto, Fernando L.; Bueno, Sérgio Luiz De Siqueira (Zootaxa, 2016)
The taxonomy of the Brazilian aeglid species Aegla paulensis Schmitt, 1942 from two disjunct hydrographic basins is revised using morphological and molecular data. Results show that six disjunctive populations of Aegla paulensis form a species complex. Aegla paulensis sensu stricto is redescribed and Aegla rosanae Campos Jr., 1998 is revalidated. The four remaining populations previously assigned to Aegla paulensis are now recognized as different species, namely Aegla  vanini n. sp., Aegla japi n. sp., Aegla jaragua n. sp. and Aegla jundiai n. sp. All new species are described and illustrated and are well supported by both morphological and molecular data. Aegla lancinhas Bond-Buckup & Buckup in Santos et al., 2015, which until recently was confounded with Aegla paulensis s. str., is supported as a valid species. A key to all members of the A. paulensis species complex is provided, and their phylogenetic and biogeographic relationships to other closely related species is discussed.